2009 16th IEEE International Conference on Image Processing (ICIP) 2009
DOI: 10.1109/icip.2009.5413426
|View full text |Cite
|
Sign up to set email alerts
|

Directional relationships to a reference object: A quantitative approach based on force fields

Abstract: A directional map (or spatial template, fuzzy landscape) is an image where the value of each pixel represents the degree to which the pixel satisfies some directional relationship (e.g., right, left, above, below) to some reference object (i.e., a given set of pixels). There exists a simple quantitative model of such relationships, and the computation of directional maps is usually based on algorithmic implementations of this model. We show here that the model has important flaws, and we respond to the issue w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, the standard fuzzy morphological dilation is computationally expensive and thus only approximate methods have been proposed [3,23] to compute it efficiently. Besides, force-fields methods have been proposed for directional relations [16,12] but they do not have the same properties and are not as generic as fuzzy-dilation-based methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the standard fuzzy morphological dilation is computationally expensive and thus only approximate methods have been proposed [3,23] to compute it efficiently. Besides, force-fields methods have been proposed for directional relations [16,12] but they do not have the same properties and are not as generic as fuzzy-dilation-based methods.…”
Section: Introductionmentioning
confidence: 99%
“…multi-core and SIMD properties of modern processors. The fuzzy dilation generates a fuzzy landscape [3] (also known as directional map [16] or spatial template [23]). In a fuzzy landscape, the value of each pixel represents to what extent it verifies the relation under study, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%